Development of sorghum plants submitted under different water table levels in glasshouse - Tanaka, Adriana Aki [UNESP]; Jadoski, Cleber Júnior [UNESP]; Klar, Antonio Evaldo [UNESP]; Silva Junior, Josué Ferreira [UNESP] (Revista Nativa, 2014)
This study aimed to evaluate the sorghum plants development (Sorghum bicolor L. Moench) submitted to different water table levels. The experiment was carried out in a glasshouse on trays with water reservoirs that allowed sub irrigation, and PVC tubes (15 cm diameter) with different heights simulating five water table levels (17 cm; 31 cm; 45 cm; 59 cm; 73 cm), treatments T1; T2; T3; T4; T5 respectively, in an entirely random design. The analyzed parameters were: fresh and dry matter, height and stem diameter of plants; fresh and dry matter and length of panicles; dry matter of roots; leaf area; crop evapotranspiration (ETc), and Kc= ETc/ETo. Water table depths between 45 and 59 cm showed significantly higher values for fresh and dry matter. The weight for fresh and dry matter and length of panicle tended to higher values for T4 and T5. There was no statistical significance among T3, T4 and T5 for stem diameter. Cultivated plants under water table closer to the surface induced plants to produce thicker stems.

O objetivo deste trabalho foi avaliar o desenvolvimento das plantas de sorgo (Sorghum bicolor L. Moench) submetidas a diferentes níveis de lençol freático. O projeto foi realizado em casa de vegetação de vidro, sobre bandejas com reservatórios de água que permitiam a subirrigação e vasos constituídos de tubos de PVC (15 cm de diâmetro) com diferentes alturas simulando diferentes níveis de lençol freático com cinco profundidades (0,17 m; 0,31 m; 0,45 m; 0,59 m; 0,73 m), tratamentos T1; T2; T3; T4; T5 e T6 respectivamente, em delineamento inteiramente casualizado. Os parâmetros analisados foram: massa da matéria fresca e seca, altura e diâmetro do colmo das plantas; massa da matéria fresca e seca e comprimento das panículas; massa da matéria seca das raízes total; área foliar; número de folhas; evapotranspiração da cultura (ETc); coeficiente da cultura (Kc). T3 e T4 foram os melhores, apresentando os maiores valores para ambas as massas, fresca e seca. Para as panículas, os maiores valores para as massas de matéria fresca e seca e comprimento foram apresentados por T4 e T5. Para o diâmetro do colmo não houve significância estatística entre T3, T4 e T5. Plantas cultivadas em níveis freáticos mais próximos da superfície induziram a produção de colmos mais grossos.
Desenvolvimento de plantas de sorgo submetidas a diferentes níveis de lençol freático em casa de vegetação
Keywords: Agronomic characteristics; Evapotranspiration; Crop coefficient; Características agronômicas; Evapotranspiração; Coeficiente da cultura